AXIOLOGICAL BASICS OF POLITICAL DEICISION-MAKING - Вінникова, Н.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The paper presents a study of the determinants of production axiological political decisions in the spectrum of trends in political governance. Outlines aspects of theoretical discourse on issues of political decision-making. Formulated methodological principles of the analysis of policy decisions through the prism of values, norms and socio-cultural factors.